Motherlove - Olsen, Tillie; Mackenzie, Midge; Women's Studies, Inc.; Women Make Movies (Firm) (New York, NY : Distributed by Women Make Movies with b&w sequences, 1980)
A personal interpretation of a portion of Tillie Olsen's story, I stand here ironing. A mother's narrative about raising her daughter, Emily, during the Depression Era, and how Emily later becomes a successful stage performer.
VHS format.
"This film was made at the Carpenter Center for the Visual Arts, Harvard University."
Production, Carter Brandon, Rob Falk, Suzanne Khuri, Laura Levine ; music, Paul Burdick.
Keywords: Short films